Smuggling routes as a valuable asset for tourism development in cross-border regions - Liberato, Pedro (2022)
Smuggling is defined as a set of clandestine exchanges of goods/products, between the population on both sides of the Portuguese and Spanish border, regardless of whether the products were legal or not, and taking advantage of the virtues of the border. It was considered a profession of risk, effort, and sacrifice, constituting an illicit import and export business between two countries, which included coffee, basic essential goods, and minerals. In these organizations, coexistence with the guards was compulsory so that the smuggled material could pass easily, and the set of daily activities generated group solidarity and collective complicity. The overall objective of this study is to understand whether smuggling tourism is a strategic tourism product in the border regions of Portugal/Galicia as tourism destinations; to evaluate its real potential and understand which routes have been carried out to promote smuggling tourism, as well as the role of population in its valuation. In the present research, it was applied a qualitative methodology, and the main data collection instrument selected was a semi-structured interview. The results show that smuggling tourism, if strategically designed, can be one of the main tourism products of the Portuguese/Spanish border. The tourist seeks to feel something similar to other people's sensations, and smuggling tourism provides these feelings, the pain, the fear, the honor, and the pride of being a smuggler. The routes recreation leads to the development of an integrated offer, and some of the companies dedicated to the subject are sponsored by municipal entities among other DMOs.